Keluhan Pelangan Dan Efektivitas Service Guarantee Di Perusahaan B2b: Dalam Perspektif Tenaga Sales - Tantri Yanuar Rahmat Syah; Z Zulhamiadi; R Rojuaniah; Ikramina Larasati Hazrati Havidz; Fadilah Nur Azizah (LPPM STIKOM Tunas Bangsa, 2023)
This study aims to examine the influence of service guarantee variables, empowerment, responsiveness in a service recovery efforts, customer satisfaction, customer loyalty on service quality. The approach used in this research is a quantitative approach. The sample used in this study were sales employees, amounting to 100 respondents. The research data was obtained from the results of filling out the questionnaire and analyzed using SEM analysis techniques with the help of the PLS SEM program. The results of this study indicate that (1) ) Service Guarantee has a positive and significant effect on service quality; (2) Service guarantee has a positive and significant effect on empowerment; (3) Empowerment has a positive and significant effect on responsiveness in service recovery efforts (4) Empowerment has a positive and significant effect on service quality; (5) Responsiveness in service recovery efforts has a positive and significant effect on service quality; (6) Service quality has a positive and significant effect on customer satisfaction; (7) customer satisfaction has a positive and significant effect on customer loyalty.